2016
DOI: 10.3390/molecules21040533
|View full text |Cite
|
Sign up to set email alerts
|

Repellent Activity of the Essential Oil from the Heartwood of Pilgerodendron uviferum (D. Don) Florin against Aegorhinus superciliosus (Coleoptera: Curculionidae)

Abstract: Abstract:The weevil Aegorhinus superciliosus Guérin (Coleoptera: Curculionidae), which is endemic to Central-Southern Chile and Argentina, is one of the major berry pests in Chile and the most important pest in the La Araucanía Region (38˝44 1 9"S, 72˝35 1 25"W). Due to the poor effectiveness and problems surrounding the implementation of the traditional control methods using organophosphate and carbamate insecticides, new strategies for controlling this pest are needed. In this communication, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…As in other species of Cupressaceae that were characterized by terpenoid biosynthesis, the composition of the PEE and DCME extracts from P. uviferum heartwood demonstrated high levels of sesquiterpenes. This agreed with chemical analyses of P. uviferum heartwood that was described in a previous study [18], which reported the presence of ten sesquiterpenes and five diterpenes in a heartwood methanol extract. In addition to this, our study identified eleven sesquiterpenes that were previously undescribed in this species.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As in other species of Cupressaceae that were characterized by terpenoid biosynthesis, the composition of the PEE and DCME extracts from P. uviferum heartwood demonstrated high levels of sesquiterpenes. This agreed with chemical analyses of P. uviferum heartwood that was described in a previous study [18], which reported the presence of ten sesquiterpenes and five diterpenes in a heartwood methanol extract. In addition to this, our study identified eleven sesquiterpenes that were previously undescribed in this species.…”
Section: Discussionsupporting
confidence: 92%
“…The EO composition of P. uviferum was obtained from Espinoza et al [18]. According to these analyses, three monoterpenes (0.43%) and 17 sesquiterpenes (86.62%) were present in EO, with torreyol (24.16%), cubenol (22.64%), 15-copaenol (15.46%), and δ-cadinene (10.81%) being the most abundant components [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations